ANALISIS MUSIKOLOGIS LAGU DALLIDEU - Sylvia Oktari; Wimbrayardi Wimbrayardi; Syeilendra Syeilendra (SENDRATASIK UNP, 2017)
This article aimed to analyze Dallideu song from the perspective of musicology.This was a qualitative research which used content analysis approach. The theory of Analysis, theory of Elements of Music, and theory of literature were used to analyze the data. The technique of data collection was begun by doing Observation, Library Studies, Interview, Labor Work (Analyzing Process) and Documentation. The result of analysis showed that Dallideu song was a song originated from oral literature (Kunaung) of Sungaipenuh community which was recorded to crystallize the old culture in the form of a song. The creation of Dallideu coincided with the birth of Dallideu Kunaung. The Dallideu song uses the major diatonic scale C = do, has 106 bars with a 4/4 beat and has a tempo of 110. The Dallideu song belongs to the 3-part A A 'B C song with the phrases a, a', c, c ', e, e '(antecedents) and the phrases b, b', d (consequences). It consists of 15 motifs (a, b, c, d, e, f, g, h, i, j, k, l, m, n, o). There are main chords (I, IV, V) and one assist chord (VII) during its chords’ develoment. Dallideu song has one kind of kadens (the perfect authentic kadens). It consists of nine phrases (a, a ', b, b', c, c ', d, e, e'). The relationship between the rhyme and melody in Dallideu song has a syllabic and melismatic form or it concerns more neither to the rhyme (logogenic) nor to the melody (melogenic).In association with the development of melody, interval, motif and rhythm of the song, the true meaning of Dallideu song is to provide a description or information from the community to the community, resembling the values contained in the song that tell thoughts and good values for the further community life. Keywords : Musicological, Analysis, Dallideu